2015
DOI: 10.18632/oncotarget.4389
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutations and polymorphisms as prognostic factors in primary glioblastoma

Abstract: Telomerase reverse transcriptase (TERT) activity is up-regulated in several types of tumors including glioblastoma (GBM). In the present study, 128 primary glioblastoma patients were examined for single nucleotide polymorphisms of TERT in blood and in 92 cases for TERT promoter mutations in tumors. TERT promoter mutations were observed in 86% of the tumors and of these, C228T (−124 bp upstream start codon) was detected in 75% and C250T (−146 bp) in 25% of cases. TERT promoter mutations were associated with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 47 publications
3
98
1
3
Order By: Relevance
“…Specifically, in thyroid cancer, our group and others reported that these mutations are associated with worse prognostic features (age of patients, tumour size and tumour stage), as well as with distant metastases, worse response to treatment and poor survival (Landa et al 2013, Liu et al 2013a,b, Melo et al 2014, George et al 2015, Qasem et al 2015, Nasirden et al 2016. TERT promoter mutations were also associated with shorter survival and/or short disease-free survival in melanomas (Griewank et al 2014, Populo et al 2014, Nagore et al 2016 and glioblastomas (Mosrati et al 2015, Simon et al 2015, Batista et al 2016, Yuan et al 2016.…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 88%
“…Specifically, in thyroid cancer, our group and others reported that these mutations are associated with worse prognostic features (age of patients, tumour size and tumour stage), as well as with distant metastases, worse response to treatment and poor survival (Landa et al 2013, Liu et al 2013a,b, Melo et al 2014, George et al 2015, Qasem et al 2015, Nasirden et al 2016. TERT promoter mutations were also associated with shorter survival and/or short disease-free survival in melanomas (Griewank et al 2014, Populo et al 2014, Nagore et al 2016 and glioblastomas (Mosrati et al 2015, Simon et al 2015, Batista et al 2016, Yuan et al 2016.…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 88%
“…Mutations in the TERT gene are thought to prevent cell senescence through increased telomere length, thus promoting tumorigenesis in several cancers, including GBM (37). The contribution of TERT mutation to tumor aggressiveness however is not clear.…”
Section: Tert Promoter Mutationmentioning
confidence: 99%
“…The contribution of TERT mutation to tumor aggressiveness however is not clear. Focusing on a sample of GBM cases, Mosrati et al found that TERT promoter mutation was associated with a shorter overall survival (37). Interestingly, this mutation was found in both primary and secondary tumors.…”
Section: Tert Promoter Mutationmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM; World Health Organization grade IV glioma) is the most common type of primary brain tumor worldwide (1). In spite of radical surgery combined with concomitant chemoradiation therapy based on temozolomide, the median survival rate of patients with GBM remains ~1 year (2).…”
Section: Introductionmentioning
confidence: 99%